WIRELESS TECHNOLOGIES for LOCATION-BASED SERVICES - Wirastuti, Dewi (Majalah Ilmiah Teknologi Elektro; Vol 11 No 1 (2012): (January - June) Majalah Ilmiah Teknologi Elektro, 2013)
This paper presents an overview of wireless technologies that support location-based services (LBS). Satellite and cellular networks have exploited their communication infrastructure to offer LBS. The rapid deployment of mobile broadband wireless networks has offered another appealing application area. Key to the realisation of LBS is an efficient and accurate positioning technique with various methods and offering different performance levels. So far, Global Positioning System (GPS) has offered the best accuracy at a low cost but it is challenged by poor indoor coverage. With the rapid deployment of broadband wireless access ubiquitously, Mobile WiMAX (Worldwide Interoperability for Microwave Access) is seen as a potential positioning option for LBS. Some key features of WiMAX, i.e., broadband benefit, high speed and large coverage area; it will be exploited to provide LBS.
Keywords: WiMAX, GPS, positioning, LBS, broadband